Assessment of lifestyle and eating habits among undergraduate students in northern Italy - Silvia Lupi; Francesco Bagordo; Armando Stefanati; Tiziana Grassi; Lucia Piccinni; Mauro Bergamini; Antonella De Donno (Istituto Superiore di Sanità, 2015)
AIM AND METHODOLOGY: Dietary habits of university students were analyzed in order to investigate any differences between students living at and away from home. Two hundred and fifty-eight undergraduate students attending University of Ferrara completed a self-administered questionnaire on demographic characteristics, food frequency consumption habits and body weight perception. RESULTS: Students living at home practiced more sport and consumed more frequently raw and cooked vegetables, fish, meat and poultry, fresh fruit, eggs, bread/cereals. Conversely, students living away from home consumed more often packaged/ready food, beer and spirits, milk and chips. The majority of students living alone reported a modification of dietary habits since leaving family. Furthermore they perceived to have a weight condition different from normal in a greater extent than students living with family. DISCUSSION: Students living alone encountered more difficulties in adopting a healthy diet so it would be desirable to adopt nutritional educational interventions on university students, usually neglected by these measures.